2014
DOI: 10.5826/dpc.0402a08
|View full text |Cite
|
Sign up to set email alerts
|

Spitz nevus on the sole of the foot presenting with transepidermal elimination

Abstract: A 10-year-old Japanese girl presented with a rhomboid-shaped brown macule, 4x3 mm in size, on the sole of the right foot. Dermoscopic examination revealed a number of black dots and globules on the ridges of the skin, marking an area of symmetrical brown pigmentation. On the periphery, a streak-like arrangement of black dots/globules on the brown pigmentation was observed along the ridges, simulating a “starburst” pattern. The lesion was excised and histological examination showed a symmetrical wedge-shaped co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The lesion was ultimately excised and determined to be a benign pigmented acral Spitz nevus. Acral nevi may also demonstrate transepidermal elimination of melanocytes, as noted in the case of a 10‐year‐old Japanese girl with a pigmented plantar lesion . This histologic finding is often associated with malignancy but has also been described in benign acral melanocytic nevi .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The lesion was ultimately excised and determined to be a benign pigmented acral Spitz nevus. Acral nevi may also demonstrate transepidermal elimination of melanocytes, as noted in the case of a 10‐year‐old Japanese girl with a pigmented plantar lesion . This histologic finding is often associated with malignancy but has also been described in benign acral melanocytic nevi .…”
Section: Discussionmentioning
confidence: 79%
“…year-old Japanese girl with a pigmented plantar lesion. 10 This histologic finding is often associated with malignancy but has also been described in benign acral melanocytic nevi. 11 In addition, histologic analysis of 158 acral melanocytic neoplasms found that the mere presence of pagetoid spread was insufficient to make a diagnosis of melanoma.…”
Section: Discussionmentioning
confidence: 90%
“…Some cases showed a starburst pattern, peripheral radial pigmentation frequently seen in SN of the non‐volar skin . Others also showed dominant pigmentation on the ridge, which may be suggestive of malignant melanoma . The heavy pigmentation in these cases might have been caused by heavy melanin deposits produced by large tumor nests of SN .…”
Section: Discussionmentioning
confidence: 91%
“…7,8 Others also showed dominant pigmentation on the ridge, which may be suggestive of malignant melanoma. 7,9 The heavy pigmentation in these cases might have been caused by heavy melanin deposits produced by large tumor nests of SN. 7 However, the macule in our case showed pagetoid melanocytic proliferation without formation of tumor nests causing heavy melanin deposits, and dermoscopy revealed relatively light, dotted linear pigmentation, some of which was distributed along either or both sides of the sulcus.…”
Section: Discussionmentioning
confidence: 98%
“…Diabetic vasculopathy induces a hypoxic state, in which the trauma from scratching causes dermal necrosis . In addition, Kobayashi et al . reported a case of Spitz naevus with transepidermal elimination, explaining this phenomenon as the mechanism of involution of the naevus.…”
Section: Reportmentioning
confidence: 99%